2021
DOI: 10.1016/j.intimp.2021.108108
|View full text |Cite
|
Sign up to set email alerts
|

Immune response variables and viral mutations impact on COVID-19 reinfection and relapse

Abstract: The possibility of human reinfection with SARS-CoV-2, the coronavirus responsible for COVID-19, has not previously been thoroughly investigated. Although it is generally believed that virus-specific antibodies protect against COVID-19 pathogenesis, their duration of function and temporal activity remain unknown. Contrary to media reports that people retain protective antibody responses for a few months, science does not exclude reinfection and disease relapse shortly after initiating all immune responses durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 140 publications
0
8
0
2
Order By: Relevance
“…The ANOVA results underscored the importance of relapses that emerged, with a small effect size. At first, SARS-CoV-2 was expected to induce a monophasic disease; however, the increasingly common cases of clinical recurrence of COVID-19 symptoms [ 60 , 61 , 62 ] have led to an investigation into whether all suspected COVID-19 relapses are due to a prolonged positive status or reinfection with a new strain [ 63 , 64 , 65 ]. Studies have indicated that clinical relapse could be due to a low level of neutralizing antibodies [ 66 ], whereas others have hypothesized that disease recurrence is due to an inflammatory syndrome because of an inappropriate immune response [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ANOVA results underscored the importance of relapses that emerged, with a small effect size. At first, SARS-CoV-2 was expected to induce a monophasic disease; however, the increasingly common cases of clinical recurrence of COVID-19 symptoms [ 60 , 61 , 62 ] have led to an investigation into whether all suspected COVID-19 relapses are due to a prolonged positive status or reinfection with a new strain [ 63 , 64 , 65 ]. Studies have indicated that clinical relapse could be due to a low level of neutralizing antibodies [ 66 ], whereas others have hypothesized that disease recurrence is due to an inflammatory syndrome because of an inappropriate immune response [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for reinfection and, more importantly, its outcome (i.e., the prognosis factors for the severity of recurrent disease) are still poorly understood [ 4 , 6 , 7 ]. It is reasonable to assume that the main risk factor for repeated infection is an insufficiently protective immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The new variants of the SARS‐CoV‐2 can bind to human cells, and the produced antibodies in the first infection could not efficiently opsonize them. Actually, these variants can lead to evading the immune response 15 …”
Section: Discussionmentioning
confidence: 99%